Breathing Life Into Dinosaurs: Tackling Challenges of Soft‐Tissue Restoration and Nasal Airflow in Extinct Species. Issue 11 (November 2014) - Bourke, Jason M.; Porter, WM. Ruger; Ridgely, Ryan C.; Lyson, Tyler R.; Schachner, Emma R.; Bell, Phil R.; Witmer, Lawrence M.; Van Valkenburgh, Blaire; Smith, Timothy; Craven, Brent; Laitman, Jeffrey T.
ABSTRACT The nasal region plays a key role in sensory, thermal, and respiratory physiology, but exploring its evolution is hampered by a lack of preservation of soft‐tissue structures in extinct vertebrates. As a test case, we investigated members of the "bony‐headed" ornithischian dinosaur clade Pachycephalosauridae (particularly Stegoceras validum) because of their small body size (which mitigated allometric concerns) and their tendency to preserve nasal soft tissues within their hypermineralized skulls. Hypermineralization directly preserved portions of the olfactory turbinates along with an internal nasal ridge that we regard as potentially an osteological correlate for respiratory conchae. Fossil specimens were CT‐scanned, and nasal cavities were segmented and restored. Soft‐tissue reconstruction of the nasal capsule was functionally tested in a virtual environment using computational fluid dynamics by running air through multiple models differing in nasal soft‐tissue conformation: a bony‐bounded model (i.e., skull without soft tissue) and then models with soft tissues added, such as a paranasal septum, a scrolled concha, a branched concha, and a model combining the paranasal septum with a concha. Deviations in fluid flow in comparison to a phylogenetically constrained sample of extant diapsids were used as indicators of missing soft tissue. Models that restored aspects of airflow found in extant diapsids, such as appreciable airflow in the olfactory chamber, were judged as more likely. The model with a branched concha produced airflow patterns closest to those of extant diapsids. These results from both paleontological observation and airflow modeling indicate that S. validum and other pachycephalosaurids could have had both olfactory and respiratory conchae. Although respiratory conchae have been linked to endothermy, such conclusions require caution in that our re‐evaluation of the reptilian nasal apparatus indicates that respiratory conchae may be more widespread than originally thought, and other functions, such as selective brain temperature regulation, could be important. Anat Rec, 297:2148–2186, 2014. © 2014 Wiley Periodicals, Inc.